Polipectomía endoscópica de colon en el niño. - Jiménez, Graciela; Fragoso Arbelo, Trini; Paniagua, Manuel; González, Nery; Grá, Bienvenido; Hernández, Walda (Revista Cubana de Pediatría, 2024)
Expone la experiencia de cinco años de trabajo.